Speak English! : the rise of Latinos in baseball - Hermoso, Rafael (Black Squirrel Books, 2013)
Latinos' experience in baseball through the decades. Latinos dominate baseball today, leading off the lineups of the best teams, making contenders strong up the middle, or helping to anchor pitching staffs. Vladimir Guerrero, Omar Vizquel, and Mariano Rivera are well-known professional baseball stars. But many Latinos had less flashy beginnings. Speak English! The Rise of Latinos in Baseball chronicles how much-- and how little--has changed since the first Latino played in the big leagues in the nineteenth century. By the middle of the next century, the Alous, Vic Power, and Rico Carty worked to earn their place in the game amid taunts and ridicule. Today, even established players and stars may be told to speak English in clubhouses--eliciting cringes or shrugs from individuals who are seemingly still hurting. Baseball Commissioner Bud Selig offers a foreword full of nostalgia and pride. The afterword by Omar Minaya describes his experience playing ball in Queens and being the first Hispanic general manager in baseball. Speak English! selects the stories of 45 players to illustrate the collective history of Latinos in baseball and is illustrated with photographic portraits of many of them. Today, more than a quarter of all major leaguers are Latino, and most began as outsiders. Globalization unearthed baseball in San Pedro de Macoris, Caguas, and Maracay. American teams looked abroad for talent and cheap wages, carving baseball diamonds out of sugarcane fields. Players in their teens left their families. Those from Cuba knew they were possibly leaving for the rest of their lives, just for the chance to play in a country still struggling with diversity in the 1950s and 1960s.